PEKERJA SOSIAL BERBASIS AGAMA DALAM PERSPEKTIF AL-QUR’AN - Ali Sodikin (Institut Keislaman Abdullah Faqih Gresik, 2021)
This paper seeks to analyze how social work can utilize religion aspect as a basic for social work practices and how the Koran’s prespectives toward social work based on religion. The paper deals particularly with the four issues as follows: (1) how is the role of religion toward social work practices; (2) how is the integration between religion and spirituality in social work practice; (3) what is the problem and challenge for religion social worker based on religion; (4) how is the opportunity and career prospect for social worker based on religion in Indonesia. The paper focuses its analysis on the social work of religion and its connection in Koran. The basic argument developed throughout this paper is that social worker can utilize religion aspect for their practices during intervention and assessment process. My paper also use Koran’s prespectives to view how is a social worker practice their ability to handle client’s case religion. Keywords: social work, religion, Koran